Influences of zero hour contracts and disability – Analysis of the 1970 British Cohort study. (September 2022) - Patel, Meet; Waynforth, David
Abstract: Rationale: In recent decades, there has been a rise of the "gig-economy" where workers are given non-standard work agreements, and work is completed in an ad-hoc nature. It was believed people this would create greater access to employment for people with disability as there would no longer be a need to disclose disability and could 'pick and choose' work. Although, little research has been done on the health-outcomes of working in non-standard agreements compared to traditional employment, and in particular it's impact on disability. Objective: This study examines one particular non-standard workplace agreement, working under zero hour contracts as the main source of income as a predictor for disability at age 46 and how income levels effect this, while controlling for pre-existing illness at age 34. Method: This study used existing data made available in the 1970 British Cohort study. Age 46 and Age 34 sweeps were used, including predictors for disability such as zero hour work, sex, and income, and binary multiple logistic regression was used. Results: This study was able to demonstrate that there is an association between working under a zero hour contract as the main source of income and disability. Further, this study shows that this association is statistically significant at low incomes but not at high incomes. Conclusions: The relationship between zero hour work and disability presented in this study may suggest that zero hour work will produce a burden on healthcare systems and limit further economic outputs by limiting individual's capacity for work. Highlights: Having a zero-hour contract as a worker's main job was associated with an increased odds of disability at age 46. Zero hours contracts were associated with disability for lower, but not for high income workers. The results suggest that zero hours work contracts pose health risks which add to the burden of disease in middle-age.